Portugal e o reino de Oere nos séculos XVI e XVII. Missionação, escravatura e intercâmbios culturais - Fonseca, Jorge (2016)
This article concerns the closed relations between Portugal and the kingdom of Oere, in the West Nigeria, during the final of the Sixteenth Century and the first half of the Seventeenth Century. These relations were based on ivory and slave trade and leaded Oere monarchs to adopt Christianity and Portuguese names and customs. The article emphasizes the stay in Portugal of the prince D. Domingos, olu’s D. Sebastião sun, which took place in the beginning of the Seventeenth Century. An unpublished document about the prince is included.